Immunomodulatory Activity of Mesenchymal Stem Cells in Lupus Nephritis: Advances and Applications - Li, Jicui; Luo, Manyu; Li, Bing; Lou, Yan; Zhu, Yuexin; Bai, Xue; Sun, Baichao; Lu, Xuehong; Luo, Ping (Frontiers in Immunology, 2022)
Lupus nephritis (LN) is a significant cause of various acute and chronic renal diseases, which can eventually lead to end-stage renal disease. The pathogenic mechanisms of LN are characterized by abnormal activation of the immune responses, increased cytokine production, and dysregulation of inflammatory signaling pathways. LN treatment is an important issue in the prevention and treatment of systemic lupus erythematosus (SLE). Mesenchymal stem cells (MSCs) have the advantages of immunomodulation, anti-inflammation, and anti-proliferation. These unique superiorities make MSCs a strong candidate for cell therapy of autoimmune diseases. MSCs can suppress the proliferation of innate and adaptive immune cells, such as natural killer cells (NKs), dendritic cells (DCs), T cells and B cells. Furthermore, MSCs suppress the functions of various immune cells, such as the cytotoxicity of T cells and NKs, maturation and antibody secretion of B cells, maturation and antigen presentation of DCs, and inhibition of cytokine secretion by a variety of immune cells, such as interleukins(IL), tumor necrosis factor(TNF), and interferons(IFN). MSCs can play an immunomodulatory role in LN through each of these immune functions. Herein we review the role of immune cells and cytokines in the pathogenesis of LN and the mechanisms involved, as well as the progress of research on the immunomodulatory role of MSCs in LN.